Controlled trial of psychotherapy for bulimia nervosa. Issue 6621 (20th February 1988) - Freeman, C P L; Barry, F; Dunkeld-Turnbull, J; Henderson, A
Abstract : In a randomised controlled trial of different types of psychotherapy for bulimia 92 women were assigned to receive cognitive-behaviour therapy (n=32), behaviour therapy (30), or group therapy (30) for 15 weeks and a further 20 (controls) assigned to remain on a waiting list for 15 weeks. Eating behaviour and psychopathology were assessed by standard methods. At the end of the trial the controls had significantly higher scores than the treated groups on all measures of bulimic behaviour. In terms of behavioural change all three treatments were effective, 71 (77%) of the 92 women having stopped bingeing. In addition, scores on eating and depression questionnaires were reduced and self esteem improved. Follow up was continuing, but of 24 women available at one year, 21 were not bingeing and had maintained their improved scores on psychometric scales. Bulimia nervosa is amenable to treatment by once weekly structured psychotherapy in either individual or group form.